Struggling Against the Bomb or Against the Bloc Divide? The Dutch Peace Movement and Eastern Europe. (2nd September 2015) - Miedema, Christie
Abstract : Between 1977 and 1985, the Dutch peace movement united against the deployment of new nuclear weapons on Dutch soil. Discussions about 'Eastern Europe', however, challenged this unity. On the one hand, in order to establish bilateral disarmament in both blocs, the leading Dutch peace group Interchurch Peace Council (IKV) looked for alliances with social movements in Eastern Europe, for instance with the Polish trade union movement Solidarność and the Czechoslovakian dissident movement Charta 77. On the other hand, the broader Dutch peace movement and church circles had doubts about this new focus, fearing that it could harm existing contacts with communist organizations and institutions. Despite these misgivings, the IKV continued to develop its policy towards Eastern Europe. Initially, it encountered opposition from communist regimes and skepticism from dissidents. Only after the disarmament struggle in the Netherlands ended in 1985 and Gorbachev opened the door for change in Eastern Europe, did the IKV succeed in establishing a more enduring contact. Nevertheless, the policy remained controversial within the Dutch peace movement and church circles as a whole.